Fábricas recuperadas e os trabalhadores: a autogestão entre a teoria e a prática - Pires, Aline Suelen (2014)
The context generated by the productive restructuring associated with financial crises and changes in the Brazilian economy in the late 1990s led to the collapse of many companies and resulted in increased unemployment and increasing instability and insecurity of labor relations. Thus, workers sought other forms of livelihood, including the associated work. ANTEAG (Associação Nacional de Trabalhadores em Empresas de Autogestão e Participação Acionária) [National Association of Self-Management Companies Workers] emerged in this context, with the goal of supporting groups of workers to unite and take control of bankrupt factories in which they worked, preserving their jobs. So, the first recovered factories emerged. At this time, the movement of the Solidarity Economy also begins to grow, and Unisol Brazil (Central de Cooperativas e Empreendimentos Solidários) [Central of Cooperatives and Solidary Enterprises] arises to support various types of solidary economic enterprises, including the recovered factories. Thus, the purpose of our research was to make a general analysis of the current situation of recovered factories in Brazil. To do this, we return to some of the pioneering experiments of recovered companies. Our goal was to understand if and how cooperative and self-managed values are present in these enterprises today. So, we performed a literature review of case studies about recovered factories and visited several experiences of this type, where we conducted observations and interviewed leaders and workers, using semi-structured scripts. In addition, we seek to look at our subject from an international perspective, so we visited Argentina and France. In general, we note that, although the ideals of cooperatives and self-management remain in the speeches of many workers, their enforcement encounters many obstacles in practice. In other words, to be viable, recuperated factories face many pressures in the market, which eventually modify some of your initial goals.